EFFECTIVENESS OF SOME INSECTICIDES AGAINST MUSTARD APHID, LIPAPHIS ERYSIMI (KALT.) (APHIDIDAE: HOMOPTERA) ON THREE DIFFERENT CROPS - Aslam, Muhammad; Ahmad, Munir (Journal of Research (Science), 2001)
Efficacy of five insecticides viz., Confidor 200 SL (imidacloprid) @ 100 ml / ha, Endosulfan 35 EC (endosulfan) @ 1500 ml / ha, Advantage 20 EC (carbosulfan) @ 750 ml / ha, Polo 500 SC (difenthiuron), @ 500 ml / ha and Trebon 30 EC (ethophenprox) @ 500 ml / ha was studied against mustard aphid, Lipaphis erysimi (Kalt.) during February 2000 on mustard (Brassica compestris L.), turnip (Brassica rapa L.) and radish (Raphanus sativus L.). All the tested insecticides controlled the aphids effectively on all the three crops, however Confidor, Endosulfan and Advantage application resulted in better control on mustard. On turnip and radish, Confidor was better than other insecticides. Maximum mortality (76 to 97%) of aphids resulted three days after application of most of the insecticides on mustard and turnip, whereas on radish, most of the insecticides gave higher mortality (84 to 98%) on seventh day after application.Where no insecticide was applied, aphid population increased 5.22, 5.15 and 3.74 times during the study period (10 days) on mustard, turnip and radish, respectively.